Peningkatan Keterampilan Sosial Peserta Didik Kelas I SDN 08 Mataram Melalui Pembelajaran Berbasis Proyek Tahun Ajaran 2022/2023 - Paramewari, Kinanti Idha; Sudarmini, Luh Ayu; Fatmawati, Elisa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
Education is one of the important things that all people should receive from the moment of their birth, growing up and until their death. Education itself must be of high quality. The very quality of education is accompanied by strengthening the social skills of students. The social skills of Grade I students are still relatively low as they tend to remain self-centered and unwilling to give in to their peers. One way teachers can improve the social skills of their students is by implementing project-based learning, commonly known as the PjBL model. This classroom action study was conducted to improve the social skills of SDN 08 Mataram Class I students through learning activities using the PjBL model. The data collection methods used in this study are observational methods and documentation methods. The data analysis in this study is a percentage description, and the data used by the researchers is students' social skills data from the observations of pre-cycle, cycle 1 and cycle 2. The results of this study are that the development of students' social skills during pre-cycle cycle is 42%. Then, after implementing training with the PjBL model, the percentage increased to 50% in the first cycle and then increased again to 61% in the cycle. This shows that the implementation of the PjBL model can improve the social skills of SDN 08 Mataram Class I students.